DELVING INTO ENGLISH SCRIPTWRITING: FROM CLASSROOM INSTRUCTION TO CREATIVE PRODUCTION - Beni Wijaya (Journal of English Educational Study (JEES), 2023)
Intended to delve into the film scripts written by English students of Politeknik Negeri Sriwijaya Palembang, twenty-three students of the Introduction to Scriptwriting course were divided into 5 groups to carry out this research. Using a qualitative approach, the scripts were collected as the instrument and then analyzed using the data analysis method proposed by Leavy (2022). The results show that thriller and mystery films are the chosen genres. While focusing on the hospitality industry, students chose housekeeping, front office, and food and beverage. There is more than one main character developed in the film's stories in many different settings such as hotels, cruises, businesses, and universities. The script lasts six to ten minutes depending on the total number of pages in the script. This study shows that the script can meet the short film standards for the hospitality industry.